Media approach to gender-based violence - Mršević Zorica (Temida)
The author grounds her research and the latter analysis on continually conducted daily press-clipping of seven main printed daily newspapers and two main electronic media in Serbia, within the three years period (2009 - 2011). An analysis of media reports on gender based violence, with particular focus on the most frequent domestic violence cases within the two years period, 2010 to 2011 is presented. As the best of media reports on gender based violence, the author stressed out its „whistle blower“ role - media are the main source of information on cases, dimensions and forms of gender based violence. Also the worse moments of media reporting in the mentioned period are presented - when the violence was justified or when reality is deformed by presenting these cases as romantic love stories. For example, in 2010 the worst was reporting on the „Pajčin/Kapisoda“ case, while in 2011 it was the „Ponjiger“ case. In the end, the author also warned on the worrysome fact of sudden dissapearance of media reports on partners’ murdering their wives after the last such report published in mid-october 2011, which could mean that now we have a new problem of diminished freedom of media.